IMPLEMENTASI TRAJECTORY PLANNINGPADA ROBOT MANIPULATOR 4 DOF UNTUK MENCARI KEBOCORAN GAS - Aditya P.P. Prasetyo; Rendyansyah; Kemahyanto Exaudi (J-Innovation, 2017)
Gas leakage in industrial areas will have negative impacts such as air pollution, loss, or even disaster. The occurrence of leakage can be caused by corrosion or from the valve crack in the pipe, and so forth. Therefore, it is necessary to have a system that can monitor the state of the gas pipeline so the possibility of leakage can be known earlier. This research has developed application of robot manipulator 4 DOF integrated with gas sensor that is MQ4 which placed at end of robot arm. The method used to determine the motion of the robot is trajectory planning in the form of cubic trajectory, where in this method the robot movement route will adjust the pattern of pipelines in cartesian coordinates. To determine the possibility of a leak of butane gas, observed the output signal from the gas sensor. If it exceeds 3.5 volts then the coordinates passed by the end-effector may leak. The experimental results show that robot manipulators with cubic trajectory planning are able to track paths according to the shape of pipes, and gas leaks can be detected by gas sensors.